1993
DOI: 10.1200/jco.1993.11.6.1124
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double-blind, placebo-controlled, dose-titration study of oral pilocarpine for treatment of radiation-induced xerostomia in head and neck cancer patients.

Abstract: It is concluded that pilocarpine produces clinically significant benefits for the symptomatic treatment of postradiation xerostomia. Best results were obtained with continuous treatment for 8 to 12 weeks with doses greater than 2.5 mg three times per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
158
0
9

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(169 citation statements)
references
References 13 publications
2
158
0
9
Order By: Relevance
“…Xerostomia after external irradiation increases the caries rate (12,13) and, thus, saliva substitutes, sialogogues (18), water, sugarless sweets, or gum are used for secondary prevention (13). Our data indicate detrimental effects on dental health also by postradioiodine xerostomia and we observed increasing tooth extraction rates with increasing cumulative radioiodine activities.…”
Section: Discussionsupporting
confidence: 54%
“…Xerostomia after external irradiation increases the caries rate (12,13) and, thus, saliva substitutes, sialogogues (18), water, sugarless sweets, or gum are used for secondary prevention (13). Our data indicate detrimental effects on dental health also by postradioiodine xerostomia and we observed increasing tooth extraction rates with increasing cumulative radioiodine activities.…”
Section: Discussionsupporting
confidence: 54%
“…Salivary production was measured and symptoms were assessed by a visual analogue scale. In both studies, pilocarpine improved symptoms compared with a placebo, but in only one (LeVeque et al, 1993) was salivary production increased to a statistically significant degree, although the volume increase was small. It is possible that qualitative differences in saliva production rather than quantitative differences helped to improve symptoms, particularly production of more mucin, which is a more long-lasting lubricant and mucosal wetting agent.…”
Section: Pilocarpinementioning
confidence: 81%
“…Two placebo-controlled double-blind trials have shown the value of this alkaloid (Johnson et al, 1993;LeVeque et al, 1993). Both multicentre studies were similar in design and contained 207 and 162 patients respectively.…”
Section: Pilocarpinementioning
confidence: 99%
“…Salivary substitutes containing methylcellulose or mucopolysaccharides may be indicated. 37,[57][58][59][60] Although they have not been evaluated in clinical trials, topical fluorides that are applied as (brushing) gels, rinses, and vacuum-formed vinyl splints loaded with fluoride gel are frequently used to prevent caries and mucositis in the course of radiotherapy because they induce fluoride incorporation into tooth enamel and dentin. They also reduce oral bacterial load.…”
mentioning
confidence: 99%